Effect of Bolting on the Face of a Crushed Soft Rock Tunnel - Chen, Lei; Cao, Yuxuan; Wen, Tongkai; Zhang, Haobin; Song, Zhanping (Directorate for Research and Community Services, Institut Teknologi Bandung, 2026)
To study the large deformation of surrounding rock during the passage of a soft rock tunnel through a fractured zone, a numerical simulation analysis was conducted on a specific tunnel section. The investigation focused on the extrusion deformation at the face, settlement deformation of the arch roof, and stress in the surrounding rock, considering the two support types used in the New Austrian Tunneling Method. The results show that the use of anchor bolts can reduce the pre-convergence deformation by 58.1% and its proportion by 23.5%, significantly increasing the minimum principal stress at the palm surface, maintaining the advanced core soil in the three-way stress state, and enhancing the longitudinal arch effect. These factors enhance the overall stability of the tunnel. Field monitoring data reveal that the convergence deformation of each part of the tunnel remains within a reasonable range, demonstrating the effectiveness of the face bolt in controlling deformation and adjusting the surrounding rock stress in the stratum, characterized by low quality and high degree of crushing.